Family caregivers’ unmet needs when caring for older people in north-east peninsular Malaysia - Makhtar, Aniawanis; Ab Ghani, Nor Nadiya (ulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2024)
Introduction Family caregivers play a vital role in supporting older people, yet their own needs are frequently overlooked, leading to unmet needs that can affect both their well-being and the quality of care provided. Addressing these unmet needs is crucial for improving care quality. Aims This study aims to examine the extent of unmet needs and identify the factors associated with unmet needs of family caregivers who are caring for older people in North-East Peninsular Malaysia. Methods A cross-sectional study was conducted among 231 family caregivers of older people, conveniently selected from two districts in Kelantan. Participants completed a questionnaire composed of sociodemographic items and a modified comprehensive needs assessment tool for caregivers. Descriptive statistics were used to summarize the data in frequencies and percentages. Independent t-tests and one-way analysis of variance were used to examine correlations among variables. Results Unmet needs were highest in the 'healthcare staff' domain, particularly the need for nurses to explain treatment or care being given to the patient. Statistically significant differences in unmet needs were observed concerning the years of caregiving, level of education, and household income (P < .05). Conclusion Recognizing and addressing the unmet needs of family members caring for older people is crucial for a holistic elder care strategy. The study highlights the importance of involving family caregivers in supporting older people. By prioritizing their needs and offering tailored support, healthcare providers can enhance outcomes for older people and improve overall family well-being.